Studi Kasus Efek Mindfulness Therapy dalam Menurunkan Stres Anak di Lembaga Pembinaan Khusus Anak Kelas II Bengkulu - Wijaya, Trio Sandra; Hidayati, Hidayati (Journal of Mental Health and Social Rehabilitation, 2024)
The phenomenon of stress experienced by juvenile correctional client frequently occurs. This is caused by various factors such as being away from family, monotonous activities in Juvenile Rehabilitation Center led to psychological issues such as stress. Therefore, researcher initiate Mindfulness Therapy Program to reduce level of stress for juvenile client. Mindfulness therapy is meditation training and conducted for eight sessions. In this study explores how the effect of mindfulness therapy to reduce child stress in the Juvenile Rehabilitation Center Class II Bengkulu. The aim is to find out the effectiveness of mindfulness therapy on reducing child stress in the Juvenile Rehabilitation Center Class II Bengkulu. This research uses a qualitative research approach and uses this type of case study research. This study consists of 5 subjects with certain criteria. The result of study shows that there is declining stress after mindfulness therapy. As a result this study is mindfulness therapy has effective effect in reducing child stress in juvenile correctional client frequently Class II Bengkulu.